Development of Children's Tourism and Promotional Activities in Uzbekistan - Shomirzayeva Nasiba Hoshimovna (Researchparks Publishing, 2022)
This article describes the importance of preschool education for children and tourism as one of the most important social, economic and cultural factors in the context of globalization and the sustainable development of markets as a type of trade services to create new jobs and the development of related industries. Given.